Investigation of some gastric Helicobacter species in saliva and dental plaque of stray cats by cultural and PCR methods - TARHANE, S.; OTLU, S. (Journal of the Hellenic Veterinary Medical Society, 2019)
The purpose of this study was to explore the presence of gastric Helicobacter species in the oral cavity of stray cats in the Kars region. Saliva and dental plaque samples collected from 100 stray cats were evaluated by culture and PCR methods in terms of gastric Helicobacter species. For culture, samples were plated on 5% defibrinated-horse blood and 5% defibrinated-sheep blood enriched selective agar plates supplemented with Vancomycin (6 μg/ml), Polymyxine B (2.500 IU/l), Trimethoprim (20 μg/ml) and Amphotericin B (2.5 μg/ml). Molecular methods were also included to study by using the PCR targeting amplification of the 16S rRNA gene sequence for Helicobactergenus and urease B gene sequence for each Helicobacter species. As the results of cultural examination, Helicobacter spp. were isolated from 10 (10%) cats (10 saliva and 5 dental plaque samples) and these were further identified as H. heilmannii by PCR. Direct analysis of samples by genus-specific PCR revealed that a total of 70 (50 saliva and 20 dental plaques) samples from 65 cats were positive in terms of Helicobacter DNA. As the results of species – specific PCR analysis of these samples 34 (48.57%) (24 saliva and 10 dental plaque samples) were identified as H. heilmannii, while the remaining 36 (51.42%) were found to be negative in terms of related species (H. heilmannii, H. pylori and H. felis). It has been concluded that these bacteria, identified in the oral cavity of the cats, may play a role in transmission of infection to humans.